The answer to this question is 120
3 to the power of 1 simplified, is just 3.
Hello,
A: roots: -1,-3
a point (-2,1)
Vertex=((-2,1)
y=k*(x+1)(x+3) using roots
but k*(-2+1)(-2+3)=1==>k*(-1)*1=1==>k=-1
eq: y=-(x+1)(x+3)
==>y=-(x²+3x+x+3)
==>y=-x²-4x-3
y=k(x+2)²+1 if x=-1,y=0 ==>k*1+1=0==>k=-1
==>y=-(x+2)²+1
Answer :A--> R,K
B)
y=k(x+4)²-2 and k=-1/2
y=-1/2(x+4)²-2
y=-1/2x²-4x-10
answer B--> I,≈W if it is written -1/2*x² (square has been forgotten)
C:
y=2x²-16x+30
y=2(x-4)²-2
answer : C-->S,J
D:
y=-(x+3)(x+1)
y=-x²-4x-3
=-(x+2)²+1
answer D--> V,L
E:
Here there is a problem: or the graph is wrong, or 2 equations are missing!
y=1(x+1)(x-3) using roots
y=x²-2x-3 ≈ T si it were -2x and not +2x.
y=(x-1)²-4 ≈H is it were -1 in place of +1 [H:y=(x+1)²-4]
2/5 in 1/12 of an hour
x in 1 hour
So multiply 12 to both fractions
2/5 x 12 in 1/12 x 12 of an hour
We get now:
24/5 in 1 hour
or:
4 4/5 in 1 hour
Answer:
A. 0
E. -3
F. 9
Step-by-step explanation:
You can't divide by 0; it is undefined. So if x cannot equal zero, then anything that turns the denominator to zero is an asymptote. Therefore, the roots of the cubic expression would be excluded, and we get our final answers.